Commitment enforcement also explains shamanism's culturally shared features. (6th April 2018) - Linquist, Stefan
Abstract: The proposed explanation for the evolution of shamanism is not the only viable option. I sketch an alternative commitment hypothesis that views shamanism as an adaptation at the level of biological individuals or cultural groups. To the extent that these hypotheses make overlapping predictions about the culturally shared features of shamanism, we lack adequate evidence to discriminate among them.